Visual Sequence Repetition Learning is Not Impaired in Signing DHH Children. (20th May 2021) - Terhune-Cotter, Brennan P; Conway, Christopher M; Dye, Matthew W G
Abstract: The auditory scaffolding hypothesis states that early experience with sound underpins the development of domain-general sequence processing abilities, supported by studies observing impaired sequence processing in deaf or hard-of-hearing (DHH) children. To test this hypothesis, we administered a sequence processing task to 77 DHH children who use American Sign Language (ASL) and 23 hearing monolingual children aged 7–12 years and found no performance difference between them after controlling for age and nonverbal intelligence. Additionally, neither spoken language comprehension scores nor hearing loss levels predicted sequence processing scores in the DHH group, whereas ASL comprehension scores did. Our results do not indicate sequence processing deficits in DHH children and do not support the auditory scaffolding hypothesis; instead, these findings suggest that factors related to experience with and/or proficiency in an accessible language during development may be more important determinants of sequence processing abilities.